The most frequently bullfrog productive systems used in Brazilian aquaculture: A review - Pahor-Filho, Eduardo [UNESP]; Mansano, Cleber Fernando Menegasso; Pereira, Marcelo Maia; De Stéfani, Marta Verardino [UNESP] (Elsevier, 2019)
Brazilian frog farming is an agricultural activity with great productive potential. Favorable climate and strong adaptation of the bullfrog to the country have led several farmers to opt for this interesting rearing activity in their rural properties, as an alternative form of income. The current review deals with the bullfrog production systems most frequently used in Brazil – Anfigranja, flooded, and cage systems. In addition to the intrinsic characteristics, we present the main studies carried out so far, as well as several suggestions for improvement of each system. From the knowledge of these data, it will be easier to understand the real situation of frog farming in the country, and the main efforts to solve its obstacles.
Keywords: Brazil; Bullfrog farming; Facilities; Feeding; Management